Condições de saúde e nutrição de usuários da rede de atenção primária à saúde, portadores de doenças crônicas não transmissíveis - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Chronic non-communicable diseases (NCDs) are a public health problem that places high demands on health services and impacts people's quality of life. The objective of this study was to perform a situational diagnosis of the health and nutrition of users of the primary health care (PHC) network with NCDs, participating in the Capacita Doenças Crônicas Project, in Ponta Grossa, Paraná. This is an epidemiological, cross- sectional, observational and descriptive study, developed with 280 users, >18 years old, from 8 basic health units (BHU) in different regions of the city (including rural areas), in which 35 users from each BHU were selected, with one or more of the three NCDs selected for the study: obesity, diabetes mellitus (DM) and/or systemic arterial hypertension (SAH). Socioeconomic and demographic data, previous health history, weight, height, medication consumption and food frequency were collected. An association was found between food consumption and socioeconomic, demographic and health condition variables. Most users were women (74.30%), whites were more frequent (75.70%) and the average age was 59.8 years. Most users were married (53.93%) and retired (38.57%). The most frequent level of education was elementary school (61.80%) and income was 1-3 minimum wages (58.90%). Regarding the diseases presented, 86.80% of users had SAD, 56.80% obesity and 42.50% DM. In addition, 63.21% had multimorbidity, 75.71% had other diseases and 97.50% mentioned medication consumption, with 27.57% in polypharmacy. The prevalence of smoking was 9.30% and 13.21% of users consumed alcoholic beverages. The most consumed foods (in average score) were natural or minimally processed foods (2.9±1.1), followed by culinary ingredients (2.8±1.7), processed foods (2.2±0.9) and, finally, ultra-processed foods (1.8±0.9). Education, housing situation and presence of DM were the variables with the highest quantity of foods or food groups with statistically significant differences in food frequency. The situational health diagnosis points to users with multimorbidity, polypharmacy and an inadequate body mass index. Although natural or minimally processed foods are the basis of the users' diet, the ingestion of ultra-processed foods is still frequent, which is influenced mainly by education and housing situation. The presence of chronic DM was associated with better eating frequency (lower consumption of ultra-processed foods). The best results found in relation to food frequency, in comparison to national surveys, may have been due to the research having involved only users with NCDs and already monitored by PHC teams.
Keywords: Unidade básica de saúde; Obesidade; Hipertensão; Diabetes Mellitus; Consumo Alimentar; Health Centers; Obesity; Hypertension; Diabetes Mellitus; Eating; CNPQ::CIENCIAS DA SAUDE